What Is a Flag For? Social media reporting tools and the vocabulary of complaint - Crawford, Kate; Gillespie, Tarleton (New Media & Society, 2014)
The flag is now a common mechanism for reporting offensive content to an online platform, and is used widely across most popular social media sites. It serves both as a solution to the problem of curating massive collections of user-generated content and as a rhetorical justification for platform owners when they decide to remove content. Flags are becoming a ubiquitous mechanism of governance—yet their meaning is anything but straightforward. In practice, the interactions between users, flags, algorithms, content moderators, and platforms are complex and highly strategic. Significantly, flags are asked to bear a great deal of weight, arbitrating both the relationship between users and platforms, and the negotiation around contentious public issues. In this essay, we unpack the working of the flag, consider alternatives that give greater emphasis to public deliberation, and consider the implications for online public discourse of this nowcommonplace yet rarely studied sociotechnical mechanism.
pre-print, published online in July 2014. Expected print publication in 2015.